Degree of conversion and polymerization shrinkage of low shrinkage bulk-fill resin composites - Haidy N Salem; Sherif M Hefnawy; Shaymaa M Nagi (Wolters Kluwer Medknow Publications, 2019)
Background: The effectiveness of each resin composite material composition in enabling homogeneous monomer conversion and reducing polymerization shrinkage (PS) is an important issue. Thus, this study aimed to evaluate the degree of conversion (DC) and PS of low-shrinkage bulk-fill composites (BFCs) in 4-mm thickness. Materials and Methods: Four bulk fill (Tetric EvoCeram Bulk Fill, Sonic Fill, XTra Fill, and Venus Bulk Fill) and one conventional (Filtek Z350 XT) resin composites were tested in this study. Teflon molds of 4-mm depth were used to prepare resin composite specimens. All tested resin composites were packed in bulk then light cured for the recommended time by their manufacturers. DC% was determined by Fourier transform infrared spectroscopy; PS was determined using the strain gauge method. Data were subjected to one-way ANOVA/Tukey's test (α = 0.05). Results: DC% results were as follows: Venus Bulk Fill > XTra Fill > Sonic Fill > Tetric EvoCeram Bulk Fill > Filtek Z350 XT with a significant difference between each others at P ≤ 0.001. For PS %, significant difference resulted between tested groups at P ≤ 0.001. Where Venus Bulk Fill < XTra Fill = Sonic Fill < Tetric EvoCeram Bulk Fill < Filtek Z350 XT. Conclusions: Low-shrinkage resin monomers seem to be beneficial for reducing PS with enhancement in the DC. Increased filler loading in BFCs had a positive effect on reducing PS, while its effect on the DC was material dependent.